The Management of Social Tensions and Community Grievances in the Albertine Region of Uganda - Ogwang, Tom (Centre for Research on Peace and Development, 2018)
Following the discovery of viable commercial oil in the Albertine region in 2006, there have been many ongoing oil related activities in that region. As a result, there have been complaints that emanate from these activities in the communities where oil and gas exploration are taking place. The oil companies in Uganda (CNOOC, Total and Tullow) finished the exploration phase and are now headed into development expected to start in 2020. Once produced, the crude oil will be partly refined in Uganda to supply the local market and partly exported to the international market. This paper focuses on emergent social tensions and conflicts linked to the advent of oil exploration and associated facilities in Uganda. Based on field research in oil producing areas, the paper seeks to provide analysis of how communities and different groups in the social structure are being affected by and are responding to the multi-facetted intrusions occasioned by the quest for oil. It also explores the various mechanisms that have evolved to address these tensions, their effectiveness; and the policy implications
Keywords: Social Tensions; Community Grievances; Uganda